2006
DOI: 10.1007/s00018-006-6300-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell adhesion by PP2A and SV40 small tumor antigen: An important link to cell transformation

Abstract: The serine/threonine protein phosphatase 2A (PP2A) represents a large family of highly conserved heterotrimeric enzymes. Their critical importance in cell homeostasis is underlined by the fact that they are targets of natural toxins like the tumor promoter okadaic acid, and of simian virus 40 small tumor antigen (SV40 small t), a viral protein known to promote cell transformation. Furthermore, mutated or lower expression levels of PP2A subunits have been found in certain cancers. One major known event in PP2A-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 146 publications
1
40
0
Order By: Relevance
“…The viral oncoproteins SV40 ST has been demonstrated to perturb critical host cell pathways, facilitating the miR-27a mediates SV40 ST-induced cell transformation Q Wang et al experimental transformation of mammalian cells (Sontag and Sontag, 2006;Sablina and Hahn, 2008). The study of SV40-induced transformation in human cell culture models has promoted the identification of pathways related to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…The viral oncoproteins SV40 ST has been demonstrated to perturb critical host cell pathways, facilitating the miR-27a mediates SV40 ST-induced cell transformation Q Wang et al experimental transformation of mammalian cells (Sontag and Sontag, 2006;Sablina and Hahn, 2008). The study of SV40-induced transformation in human cell culture models has promoted the identification of pathways related to cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PP2A influences TJ biogenesis by negatively regulating the activity of aPKC and by controlling the phosphorylation state of TJ proteins (28,31). Therefore, distinct serine/threonine phosphatases apparently target different TJ components, allowing the dynamic modulation of epithelial barriers in response to physiological or pathological stimuli (32).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of PP2A as a multifunctional modulator, molecular regulation of PP2A activity by the intrinsic and/or extrinsic signal network decides the cell's destination. Previous studies demonstrated that the Simian virus 40 small T antigen (SV40 ST), directly inhibits the activity of PP2A in promoting cell transformation (35). On the other hand, oncogenic signals enhanced by nonreceptor-and receptor-linked tyrosine kinases including the EGFR and the insulin receptor stimulate tyrosine phosphorylation of PP2A and thereby inhibit its activity (19).…”
Section: Discussionmentioning
confidence: 99%